The Family Life That John Berry Had But Never Experienced - Venable Palmer, Cozy; Kehoe, Michael (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
Two genealogists, Cozy Palmer in Dallas, Texas and Mike Kehoe in Richmond, Utah, unbeknownst to each other, were simultaneously researching the family of John Berry who fought and was captured at the Battle of the Windmill in 1838 and were not making much progress. Together, their research has led to a better understanding of the life of John Berry prior to his involvement in the Patriot War and to the discovery of the life that John Berry could have had if it were not for his involvement in the conflict.